Two Rare Variants of Down Syndrome: Down-Turner Syndrome and Down Syndrome with Translocation (13;14): A Case Report - Evren GUMUS (Tehran University of Medical Sciences, 2019)
In the present paper, we report two rare cases of Down syndrome (DS); mosaic Down-Turner syndrome and DS with rob (13;14). Patient 1 karyotype is mos 45,X[41] / 47, XX,+21[59] and patient 2 karyotype is 46, XY, rob (13;14)(q10;q10),+21. With these two unusual cases, we aimed to look at the most common numerical and structural chromosome anomalies from a different window and evaluate the phenotypic effect in the presence of different chromosomal anomalies. Our main goal is to evaluate the phenotypic characteristics of these two rare variants in the light of literature.